Análise do desenvolvimento de habilidades comunicativas de uma criança autista e filha de pais surdos - Andrade, Cássio Kennedy de Sá (2022)
Children with Autism Spectrum Disorder (ASD) have characteristics that differ from other subjects with typical development; among these particularities are difficulties in socialization and language use. Children with autism often also have a deficit in joint attention. However, according to Tomasello (2003), such skill is essential for establishing communication with people, since joint attention permeates the interaction between subjects, which makes it a basic skill for language acquisition. For individuals with ASD to enter the universe of communication, it is often necessary to use facilitating methods, tools that can help individuals with communicative difficulties to express themselves. Thus, Alternative and Augmentative Communication (AAC) tries to meet the communicative needs of subjects with language disorders by offering them communication options that replace and/or complement speech. In this sense, the main objective of this study is to verify the development of the communicative abilities of a child with ASD, aged 5 years, daughter of deaf parents. For this, the choice of the DHACA method (MONTENEGRO, 2020) for the implementation of an Augmentative and Alternative Communication system was analyzed. For that, it became necessary to describe the way in which the interactions between the child with ASD and their interactants occurred, through the capture of videos and analysis of the Planning and Evolution Diaries used in each speech therapy session. Data from this research were obtained during the sessions at the speech therapy clinic and at times at the home of the child with ASD. The multimodal resources present in the interactions were also analyzed, using the Children's Multimodal Assessment Protocol (LIMA, 2020), as well as the protocols used and applied during the child's speech therapy care. The data were described and analyzed in a qualitative and interpretative way, and descriptively, through statistical analyses. In this way, it became possible to point out the contributions of the DHACA method for the development of the communicative skills of children with ASD, as well as the process of using AAC, which was initially conceived only in Portuguese and then was reformulated including LIBRAS. After the data were studied, it was noticed that the DHACA method enabled the development of communicative skills in the child in question. With the use of the bilingual AAC board, significant improvements were noticed in the ability of joint attention, considerably increasing the number of spontaneous interactions, the use of symbolic games, imitation, the use of gestures and vocalizations. Therefore, the effectiveness of the DHACA method is proven, which can be indicated for intervention in other individuals who need to have their communicative skills improved.